Effectiveness of Lime (Citrus amblycarpa) Solution in Improving the Bacteriological Quality of Tableware - Faridah, Faridah; Isnawati, Isnawati; Noraida, Noraida; Rahmawati, Rahmawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
According to research on cutlery, it did not meet the bacteriological quality requirements for cleanliness because the disinfection process was not carried out. nfection process is necessary to enhance the cleanliness of cutlery, employing both chemical and natural methods. Lime zest is a natural ingredient that can be used for disinfection because it contains compounds such as alkaloids, tannins, steroids, triterpenoids, saponins, and flavonoids that are antibacterial by damaging cell membranes. The study's goal was to determine the efficacy of lime (Citrus amblycarpa) solution in improving the bacteriological quality of cutlery. This research is experimental, with a posttest-only control group design. The study included a total of 24 cutlery (plate) samples. We collected the data by examining the number of germs and Escherichia coli in each sample. Using Kruskal-Wallis, we analysed bacterial count data. Meanwhile, Escherichia coli could not be tested because all the samples were negative. The results showed that the cutlery (plate) before treatment did not contain Escherichia coli. By taking swab samples of the cutlery (plates), we found that the number of germs after disinfection treatment ranged from 1 to 33 colonies/cm2. Lime solution is ineffective at reducing the number of germs. It is recommended that the shop manager use running water and provide a place for draining and storing closed cutlery. Future researchers can conduct laboratory tests first to prove the effect of lime zest on Escherichia coli and carry out control treatments before concentration treatments.